Hybrid Microporous Polymeric Materials with Outstanding Permeability and Increased Gas Transport Stability: PTMSP Aging Prevention by Sorption of the Polymerization Catalyst on HCPS - Golubev, Georgy (Polymers (Basel), 2021)
The influence of hyper-crosslinked polystyrene (HCPS) Macronet(TM) MN200 on the gas transport properties and aging of the highly permeable glassy polymer poly(1-trimethylsilyl-1-propyne) (PTMSP) was studied and analyzed in detail. The gas transport characteristics of dense PTMSP membranes containing 0–10.0 wt % HCPS were studied. It was shown that the introduction of a small amount of HCPS into the PTMSP matrix led to a 50–60% increase of the permeability coefficients of the material for light gases (N(2), O(2), CO(2)) and slowed down the deterioration of polymer transport properties over time. The lowest reduction in gas permeability coefficients (50–57%) was found for PTMSP containing HCPS 5.0 wt % after annealing at 100 °C for 300 h. It was found that HCPS sorbed residues of tantalum-based polymerization catalyst from PTMSP. In order to investigate the influence of catalysts on transport and physical properties of PTMSP, we purified the latter from the polymerization catalyst by addition of 5 wt % HCPS into polymer/chloroform solution. It was shown that sorption on HCPS allowed for almost complete removal of tantalum compounds from PTMSP. The membrane made of PTMSP purified by HCPS demonstrated more stable transport characteristics compared to the membrane made of the initial polymer. HCPS has a complex effect on the aging process of PTMSP. The introduction of HCPS into the polymer matrix not only slowed down the physical aging of PTMSP, but also reduced chemical aging due to removal of active reagents.